2015
DOI: 10.1189/jlb.3vma1014-482r
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived MRP-14 is up-regulated in infectious osteomyelitis and stimulates osteoclast generation

Abstract: Bone infections of patients with joint replacement by endoprosthesis (so called “periprosthetic joint infection”) pose a severe problem in the field of orthopedic surgery. The diagnosis is often difficult, and treatment is, in most cases, complicated and prolonged. Patients often require an implant exchange surgery, as the persistent infection and the accompanying inflammation lead to tissue damage with bone degradation and consequently, to a loosening of the implant. To gain insight into the local inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 39 publications
0
30
0
3
Order By: Relevance
“…1 The latest data 2 suggests that inflammation plays a critical role in bone remodeling and in pathogenesis of osteoporosis. The present study 3 describes the neutrophil as a cell that acquires roles beyond that of a prototypic inflammatory cell, directly capable of activating osteoclasts. Blood neutrophil lymphocyte ratio (NLR) is a non-invasive, simple and cost-effective marker of inflammation in various malignancies and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1 The latest data 2 suggests that inflammation plays a critical role in bone remodeling and in pathogenesis of osteoporosis. The present study 3 describes the neutrophil as a cell that acquires roles beyond that of a prototypic inflammatory cell, directly capable of activating osteoclasts. Blood neutrophil lymphocyte ratio (NLR) is a non-invasive, simple and cost-effective marker of inflammation in various malignancies and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Following this notion further, we evaluated expression of inflammatory cytokines in tissue samples and found that certain cytokines—chiefly CXCL8 (IL-8), CCL3 and CXCL2 (the macrophage inflammatory proteins MIP1α and MIP2α), and S100A9 (MRP14)—were elevated in patients suffering from implant infections [34,35,36]. Since MRP14 is an abundant content in neutrophils, we also investigated MRP14 plasma concentrations and found these to be elevated, advocating MRP14 as a promising future diagnostic marker in peripheral blood [35].…”
Section: Systemic and Local Immune Response In Biofilm Infectionsmentioning
confidence: 99%
“…Since MRP14 is an abundant content in neutrophils, we also investigated MRP14 plasma concentrations and found these to be elevated, advocating MRP14 as a promising future diagnostic marker in peripheral blood [35]. …”
Section: Systemic and Local Immune Response In Biofilm Infectionsmentioning
confidence: 99%
“…Despite serum CRP and ESR are recommended as the diagnostic criteria by Musculoskeletal Infection Society (MSIS) [3] and commonly checked for PJI diagnosis [3], they do not work well in situations including chronic [4] and low virulence organism infections [1,2]. In the past a few years, the meaning of numerous blood markers such as serum soluble intercellular adhesion molecule-1 (sICAM-1) [5], myeloidrelated protein14 (MRP-14) [6], soluble urokinase plasminogen activation receptor (su-PAR) [7] and lipopolysaccharide-binding protein (LBP) [8,9] have been tesetd in PJI diagnosis, . Although some of these markers showed good performance in PJI diagnosis, due to high expense and special antibodies, it is not possible to prevail them in clinical practice especially in primary hospitals in the near a few years.…”
Section: Introductionmentioning
confidence: 99%